2021
DOI: 10.3390/ma14195627
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and Impact Toughness Properties of a Zr-Based Bulk Metallic Glass Fabricated via Laser Powder-Bed Fusion

Abstract: In the past few years, laser powder-bed fusion (LPBF) of bulk metallic glasses (BMGs) has gained significant interest because of the high heating and cooling rates inherent to the process, providing the means to bypass the crystallization threshold. In this study, (for the first time) the tensile and Charpy impact toughness properties of a Zr-based BMG fabricated via LPBF were investigated. The presence of defects and lack of fusion (LoF) in the near-surface region of the samples resulted in low properties. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The highest fracture strength measured was 1326 MPa. Sohrabi et al [100] investigated the tensile performance of LPBF-fabricated AMZ4 BMG samples, and a high fracture strength of 1180 MPa was obtained, although no macro plastic deformation was detected in the tensile tests. It was also found that the loading direction has a noteworthy influence on the fracture strength of LPBF-fabricated BMG specimens, which may be related to the layered structure obtained with 3D printing.…”
Section: Tensile Behaviormentioning
confidence: 99%
See 3 more Smart Citations
“…The highest fracture strength measured was 1326 MPa. Sohrabi et al [100] investigated the tensile performance of LPBF-fabricated AMZ4 BMG samples, and a high fracture strength of 1180 MPa was obtained, although no macro plastic deformation was detected in the tensile tests. It was also found that the loading direction has a noteworthy influence on the fracture strength of LPBF-fabricated BMG specimens, which may be related to the layered structure obtained with 3D printing.…”
Section: Tensile Behaviormentioning
confidence: 99%
“…There has been very little research into the tensile properties of LPBF-prepared BMGs, with only three studies reported so far, and all of them were carried out on the industrialgrade alloy Zr 59.3 Cu 28.8 Al 10.4 Nb 1.5 (AMZ4) BMG [99][100][101]. Best et al [101] conducted tensile tests on LPBF-fabricated AMZ4 BMG, and the samples underwent a typical brittle fracture with a fracture strength of only 1.08 GPa, which is considerably lower than the compressive strength of the material of 1.8 GPa [82], as shown in Figure 12.…”
Section: Tensile Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…As predominantly brittle intermetallic phases crystallize in the HAZ, a significant detrimental impact on the mechanical response, particularly upon deformation at room temperature is observed. [50][51][52][53][54] Some authors exploit (B2 to B19) martensitic to enhance the plastic deformability of bulk metallic glass composites (BMGCs). However, even for those systems, crystallization and consequently reduced ductility remain a challenge for the printing of BMGs.…”
Section: Introductionmentioning
confidence: 99%